Comparison of the membrane composition of Spiroplasma citri and the corn stunt Spiroplasma. - Mudd, J B (1979)
Components of membranes isolated from Spiroplasma citri and corn stunt spiroplasma grown at 28 degrees C were analyzed. On a protein basis, lipid phosphorus was lower and cholesterol was higher in S. citri. Only minor differences between the two species were found in fatty acid composition, reduced nicotinamide adenine dinucleotide diaphorase, and adenosine triphosphatase.